2003
DOI: 10.1142/s0218202503002362
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Analysis of a Mathematical Model for Capillary Formation in Tumor Angiogenesis

Abstract: Qualitative analysis of a mathematical model for capillary formation is presented under assumptions that enzyme and fibronectin concentrations are in quasi-steady state. The aim of this paper is to prove mathematically that the long-time tendency of endothelial cells will be towards the transition probability density function of enzyme and fibronectin. Endothelial cell steady-state solution is obtained and a numerical simulation is provided to show that there is a close agreement between the steady-state solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…The result we have obtained in Eq. (11) agrees with the result obtained in [6]. Therefore, we now have…”
Section: Stability Analysis Of the Steady-statesupporting
confidence: 91%
See 2 more Smart Citations
“…The result we have obtained in Eq. (11) agrees with the result obtained in [6]. Therefore, we now have…”
Section: Stability Analysis Of the Steady-statesupporting
confidence: 91%
“…(1) is an equation for Endothelial cell migration in Tumor angiogenesis. We have shown that this simpler model, consisting of a single pde for the endothelial cell density, captures almost all of the features of the original model [4,6]. The analysis performed on the model has permitted us to focus upon the behaviour of the endothelial cells at the capillary.…”
Section: Stability Analysis Of the Steady-statementioning
confidence: 97%
See 1 more Smart Citation
“…Theoretical nonlinear analyses of various tumour models mentioned above have been performed (e.g. [53, 78, 122, 131134, 136142, 155, 182, 199, 202204, 207, 208, 389, 404, 480, 515, 517, 539, 558, 562, 564, 576, 577]). Recently, mixture models have been developed that are capable of describing the detailed interactions among multiple solid (cell) species and extra-/intra- cellular liquids (see section 2.5).…”
Section: Continuum Modellingmentioning
confidence: 99%
“…Over the last few years, so many mathematical models of tumor growth have appeared in the research literature, for example, see [1][2][3][4][5][6]. In this paper, we shall consider the following parabolic equation:…”
Section: Introductionmentioning
confidence: 99%